Regulating sustainable minerals in electronics supply chains: local power struggles and the ‘hidden costs’ of global tin supply chain governance - Diprose, Rachael; Kurniawan, Nanang; Macdonald, Kate; Winanti, Poppy Sulistyaning (Taylor & Francis, 2022)
Voluntary supply chain regulation has proliferated in recent decades in response to concerns about the social and environmental impacts of global production and trade. Yet the capacity of supply chain regulation to influence production practices on the ground has been persistently questioned. Through empirical analysis of transnational regulatory interventions in the Indonesian tin sector—centered on a multi-stakeholder Tin Working Group established by prominent global electronics brands—this paper explores the challenges and limits of voluntary supply chain governance as it interacts with an entrenched ‘extractive settlement’ in Indonesia’s major tin producing islands of Bangka and Belitung. Although the Tin Working Group has introduced localized initiatives to tackle issues such as worker safety and improved land rehabilitation, it has also contributed in diffuse and largely unintended ways to consolidating the power of political and economic elites who benefit from centralized control over resource extraction. In this sense, supply chain governance has generated ‘hidden costs’ through unintended effects on power struggles between competing social groups at national and sub-national levels—generating marginal benefits for ameliorating specific regulatory ‘problems’, while consolidating and reproducing barriers to deeper transitions towards inclusive or sustainable regimes of extractive governance.